Antlions of southern Africa: Syngenes Kolbe, 1897, with descriptions of two new species and comments on extra-limital taxa (Neuroptera: Myrmeleontidae: Acanthaclisini) - Mansell, Mervyn W. (Zootaxa, 2018)
The southern African species of Syngenes Kolbe, 1897, are revised and compared with their Afrotropical congeners. Three species occur in the region: S. longicornis (Rambur, 1842) and two new species, S. medialis and S. scholtzi, described and illustrated below. A key to the Afrotropical taxa is provided. The larva of S. longicornis is illustrated. The genus is widespread in the Afrotropical Region and extends to the Middle East and Oriental Region. Syngenes species are typically broad-winged antlions, with irregular bifurcate and biaereolate cells between the costa and subcostal veins, which distinguish them from other members of the tribe Acanthaclisini.